Increasing the role of educational literature in the educational system of bachelor’s and master’s degrees - Makhanov М. Маханов М.; Abdikerimova G. Абдикеримова Г.Б. (Рroblems of engineering and professional education, 2023)
This article highlights the state and insufficient provision of technical books of high schools published in the Kazakh language. Questions are considered about the difference between textbooks and teaching aids recommended for undergraduate and graduate programs, problems of improving their level and quality.